2004
DOI: 10.1515/jpem.2004.17.10.1443
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Iron Status and Thyroid Hormones in Adolescents Living in an Iodine Deficient Area

Abstract: Background: Iron may be only one of many nutritional factors that influence thyroid hormone metabolism in iodine-deficient areas. Objective: To evaluate the effect of iron status on thyroid hormone profile in adolescents living in a mild iodine-deficient area in Turkey. Subjects: Three hundred and thirty school-aged children with mean age 14 years were examined. Methods: Free triiodothyronine, free tetraiodothyronine and thyrotropin levels were analyzed by chemiluminescent enzyme immunoassay. Hemoglobin and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…Increased serum T3 and decreased resin T3 uptake was present in those with lower serum ferritin levels; however, free T3 and T4 index, serum T4 and TSH were not significantly different between those with low and normal ferritin. Yavuz et al (2004) evaluated the effect of iron status on thyroid hormone profile in adolescents living in a mildly iodinedeficient area in Turkey, and found that thyroid hormone levels of the children with anemia were not significantly different compared to children without anemia. No significant correlation was found between thyroid hormones and iron status.…”
Section: Resultsmentioning
confidence: 99%
“…Increased serum T3 and decreased resin T3 uptake was present in those with lower serum ferritin levels; however, free T3 and T4 index, serum T4 and TSH were not significantly different between those with low and normal ferritin. Yavuz et al (2004) evaluated the effect of iron status on thyroid hormone profile in adolescents living in a mildly iodinedeficient area in Turkey, and found that thyroid hormone levels of the children with anemia were not significantly different compared to children without anemia. No significant correlation was found between thyroid hormones and iron status.…”
Section: Resultsmentioning
confidence: 99%
“…Bivolarska A et al, reported the firm association between T4 level and Hb (r= 0.217, p=0.33), on the other hand some other study like Yavuz O et al, reported no association between thyroid hormone and iron deficiency. 24 Thus, subclinical hypothyroidism and iron deficiency anemia are interdependent entities who do not come to notice until the vicious cycle augments both the disease processes. Given the overt nature of subclinical hypothyroid state, all patients presenting with iron deficiency should be evaluated for thyroid dysfunction, and all subclinical hypothyroid patients should undergo evaluation for iron deficiency and treated accordingly to break the vicious cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have provided equivocal outcomes. While a few studies found no significant association between serum thyroid hormone concentrations and iron status (93,94), others had different results. Lower serum T4 and/or T3 and higher TSH levels were reported in women with iron-deficiency anemia than in non-anemic controls, and iron supplementation partially normalized plasma thyroid hormone concentrations (95,96).…”
Section: Iron Deficiency Affects Thyroid Metabolismmentioning
confidence: 99%